Correction: Contrasting mechanisms for hidden hearing loss: Synaptopathy vs myelin defects. - Maral Budak; Karl Grosh; Aritra Sasmal; Gabriel Corfas; Michal Zochowski; Victoria Booth (PLoS Computational Biology)
[This corrects the article DOI: 10.1371/journal.pcbi.1008499.].